1995
DOI: 10.1021/bi00016a009
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl sulfide and carbon dioxide as new substrates, and carbon disulfide as a new inhibitor, of nitrogenase

Abstract: Nitrogenase is the metalloenzyme responsible for the biological reduction of N2 to NH3. Nitrogenase has been shown to reduce a variety of substrates in addition to N2 and protons. General properties of alternative substrates for nitrogenase are the presence of N-N, N-O, N-C, and C-C triple or double bonds. In the present work, we demonstrate that Azotobacter vinelandii nitrogenase can reduce both C-S and C-O bonds. Nitrogenase was found to reduce carbonyl sulfide (COS), to CO and H2S at a maximum rate of 37.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 43 publications
6
106
4
Order By: Relevance
“…The observation that ΔnifH MoFe protein is capable of reducing CO to hydrocarbons raises the question of whether this protein can generate hydrocarbons from CO 2 , particularly given the previous observation that the wild-type MoFe protein can reduce CO 2 to CO (21). Indeed, when a mixture of carbon dioxide/bicarbonate (CO 2 /HCO 3 − ) is used as a substrate, C 2 H 4 , C 2 H 6 , C 3 H 6 , and C 3 H 8 are detected as products in the Eu(II)-DTPA-driven, ΔnifH MoFe protein-based reaction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that ΔnifH MoFe protein is capable of reducing CO to hydrocarbons raises the question of whether this protein can generate hydrocarbons from CO 2 , particularly given the previous observation that the wild-type MoFe protein can reduce CO 2 to CO (21). Indeed, when a mixture of carbon dioxide/bicarbonate (CO 2 /HCO 3 − ) is used as a substrate, C 2 H 4 , C 2 H 6 , C 3 H 6 , and C 3 H 8 are detected as products in the Eu(II)-DTPA-driven, ΔnifH MoFe protein-based reaction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of enzymes besides CA have affinity to OCS as a substrate, such as RuBisCO (Lorimer & Pierce, 1989), carbon monoxide dehydrogenase (Ensign, 1995), nitrogenase (Seefeldt et al, 1995), OCS 15 hydrolase (Ogawa et al, 2013), and CS 2 hydrolase (Smeulders et al, 2011), but their impact on total soil OCS consumption has not been assessed. A few studies have linked specific microbial groups, including T. thioparus (Ogawa et al, 2013), Actinobacteria (Kato et al, 2008;Ogawa et al, 2016), and Ascomycota (fungi) (Masaki et al, 2016), to the degradation of atmospheric OCS.…”
Section: Ocs To Probe Variables Other Than Gppmentioning
confidence: 99%
“…Seefeldt and co-workers have shown that CO 2 is slowly reduced to CO by the nitrogenase enzyme. 58 Complexes 1a and 1b each react with 2 equiv of carbon dioxide at room temperature, generating yellow solids that are formulated as formate-bridging diiron complexes (10a, 10b) based on X-ray crystallography (Figure 10). Only a few crystallographically characterized η 2 -formato bridging iron complexes have been reported in the literature.…”
Section: Ironmentioning
confidence: 99%